Childhood Adversity and Herpesvirus Latency in Breast Cancer Survivors - Fagundes, Christopher P. (2012)
OBJECTIVE: Childhood adversity has been linked to greater emotional and physiological sensitivity to stress. Stress has well-documented effects on cellular immunity, including enhanced herpesvirus reactivation. This study assessed whether childhood adversity was associated with the expression of two latent herpesviruses, Epstein-Barr virus (EBV) and cytomegalovirus (CMV) in adults, and whether this association could be detected beyond the psychological distress women experienced in the aftermath of a breast cancer diagnosis and its treatment. METHODS: One hundred and eight breast cancer survivors completed questionnaires and provided blood samples to assess EBV virus capsid antigen (VCA) IgG antibody titers and CMV IgG antibody titers. RESULTS: Breast cancer survivors who experienced more childhood adversities had higher EBV and CMV antibody titers than those with fewer childhood adversities. Those who experienced more childhood adversities also had more depressive symptoms, less education, and poorer sleep quality than those with fewer childhood adversities. Depressive symptoms, education, sleep quality, age, BMI, cancer stage, comorbidities, and weekly alcohol consumption were not related to EBV or CMV antibody titers. Time since last treatment was negatively associated with EBV and CMV antibody titers. Elevated antibody titers to latent herpesviruses represent poorer cellular immune system control over viral latency; these data suggest that those with more childhood adversities have poorer cellular immune function. CONCLUSION: These findings add to the emerging literature suggesting that adverse early experiences may make people more vulnerable to immune dysregulation in adulthood. The consequences of early adversity appear to persist across the lifespan.